دراسة تصنيفية لبعض أنواع جنس L. Ophrys من الفصيلة السحلبية Orchidaceae ضمن محافظة اللاذقية – سورية - عشي, ميرنا; حداد, دينا; حمدان, مها (Latakia University Journal -Biological Sciences Series, 2019)
أكدت الدراسة التصنيفية لجنسOphrys في محافظة اللاذقية على وجود نوعين هما: Oph. fusca Link., Oph. lutea Cav. وتم تسجيل 4 أنواع لأول مرة في سورية وهي: Oph. sphegodes Miller., Oph. transhyrcana Czernjak., Oph. umbilicata Desf., Oph. apifera Hudson. حيث لم تشر أي من الدراسات السابقة إلى وجودها في الفلورا السورية. تم التمييز بين الأنواع بالاعتماد على الصفات المورفولوجية للنورة، والزهرة من حيث: الشفة، والسداة المأنثية، والطلعات، والمبيض، والميسم. أوضحت دراسة حبات الطلع في الأنواع المدروسة أنها بيضوية الشكل ووحيدة ثقب، وبلغت سماكة الغلاف(1.923) ميكرومتر وقطر الثقب(3.846) ميكرومتر. الثمار في الأنواع المدروسة كبسولة (علبة)، والبذور غبارية المظهر وجناحية الشكل مع وجود اختلاف في الحجم لكل من الثمار والبذور. The classification study of some Ophrys genus in Lattakia emphasizes that there are two kinds Ophrys fusca Link., Ophrys lutea Cav. Four new kinds were registered for the first time in Syria: Ophrys sphegodes Miller., Ophrys transhyrcana Czernjak.,Ophrys umbilicata Desf., Ophrys apifera Hudson. Previous studies of Syrian Flora have not mentioned any of them. A differentiation has been done between these kinds according to the morphological Inflorecense, and flower including Labellum, gynostenium, pollinium, ovary, stigma. The pollen study in the studied species clarified that they have oval shape and mono hole. The thickness of wall is 1.923 µm and diameter of the pollen grain hole is about 3.846 µm. Fruit is capsule. Seeds are innumerable, tiny, and powder like, with differences in size of both fruits and seeds.